2003
DOI: 10.1046/j.1432-1033.2003.03869.x
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystokinin rapidly stimulates CrkII function in vivo in rat pancreatic acini

Abstract: Crk belongs to a family of adapter proteins whose structure allows interaction with tyrosine-phosphorylated proteins and is therefore an important modulator of downstream signals, representing a convergence of the actions of numerous stimuli. Recently, it was demonstrated that cholecystokinin (CCK) induced tyrosine phosphorylation of proteins related to fiber stress formation in rat pancreatic acini. Here, we investigated whether CCK receptor activation signals through CrkII and forms complexes with tyrosine-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
7
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
4
7
0
Order By: Relevance
“…However, the relative importance of activation of the high and low affinity CCK 1 receptor state differs among these proteins. In contrast to these results, CCK-mediated activation in pancreatic acini of phospholipase D or PI3K requires activation of only the high affinity receptor state [49], whereas in the case of PKC-δ [6] or CRK-II [50] only the low affinity CCK 1 receptor state is required for activation. Also, in contrast to our results with Yes activation, a previous study [3] reported CCK-stimulated SFK activity is mediated almost entirely by activation of the low CCK 1 receptor state in pancreatic acini.…”
Section: Discussionmentioning
confidence: 99%
“…However, the relative importance of activation of the high and low affinity CCK 1 receptor state differs among these proteins. In contrast to these results, CCK-mediated activation in pancreatic acini of phospholipase D or PI3K requires activation of only the high affinity receptor state [49], whereas in the case of PKC-δ [6] or CRK-II [50] only the low affinity CCK 1 receptor state is required for activation. Also, in contrast to our results with Yes activation, a previous study [3] reported CCK-stimulated SFK activity is mediated almost entirely by activation of the low CCK 1 receptor state in pancreatic acini.…”
Section: Discussionmentioning
confidence: 99%
“…Our results with PAK2 activation are similar to the CCK-induced activation of the Src kinases(Lyn, Yes)[41,78], the focal adhesion kinases (p125FAK, PYK2)[34,39], paxillin[34,40] and PKD[54] in pancreatic acini[78], that are all mediated by activation of both high- and low-affinity receptor-states, although with differences in their relative importance. In contrast to these results, CCK-mediated activation in pancreatic acini of phospholipase D or PI3K requires activation of only the high-affinity receptor-state[97], whereas in the case of PKC-δ [32] or CRK-II[98], only the low-affinity CCK 1 receptor-state is required for activation. Also, a previous study[99] reported CCK-stimulated SFK activity is mediated almost entirely by activation of the low-CCK 1 receptor state in pancreatic acini.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the high affinity CCK A receptor state is responsible for only 20% of the maximal activation of PKCmu (PKD1) [18] and PYK2/CAKβ [17], whereas it mediates 50% of the maximal stimulation of p125 FAK and paxillin phosphorylation [65] and mediates 60% of Lyn activation [64]. These results with PKCθ activation differ from results seen with CCK activation in pancreatic acinar cells of the novel PKC, PKCδ [14] or stimulation of phosphorylation of the adaptor protein, CrKII, [66] where are mediated only through activation of the low affinity CCK A receptor state. In contrast, CCK-mediated activation of PI-3 kinase and phospholipase D in pancreatic acinar cells is mediated entirely by the activation of the high affinity receptor state [67].…”
Section: Discussionmentioning
confidence: 99%